(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Psychosis is a basic concept in psychiatry. It used to be the same name for all kinds of mental illnesses. Today, the term describes an ill-defined complex symptom (syndrome) characterized by hallucinations, delusions, loss of reality, or ego disturbances. In some diseases, affective symptoms are also associated with psychoses. These different symptoms can occur individually or in combination. Psychoses can occur in various diseases. Diagnosis of the disease is possible only through careful diagnosis. Therapy depends on the disease and symptoms. If there is no self-healing, treatment is often carried out with neuroleptics.